On the Terminological Issue of Describing Resurrection as ‘Physical’ - Harriman, K. R. (The Evangelical quarterly, 2022)
From the early centuries of the church, there has been much discussion on how best to describe Jesus’s resurrection and the expected eschatological resurrection (particularly of believers). One popular way of describing resurrection has been as ‘physical’, which in some ways corresponds with the ancient description of the resurrection ‘of the flesh’. Critics of this approach have, in fact, treated these descriptions as synonymous and have argued that ‘physical’ is not an apt adjective for describing Jesus’s or the eschatological resurrection. I argue here, particularly by reference to 1 Cor. 15, that it remains appropriate to refer to resurrection according to the Bible as ‘physical’, not as ‘bodily, but not physical’, and that it is the critics who have overcomplicated the term by making it entail what it does not entail and have thus provided obfuscation where they claimed to provide clarification.